On the validity of 2D analysis of non-isothermal sintering in SLS. (23rd February 2020) - Balemans, Caroline; Hulsen, Martien A.; Anderson, Patrick D.
Highlights: Direct numerical simulation of the sintering of two particles in 3D. Accurate description of heat transfer and temperature-dependent viscous flow. Scaling guidelines to apply 2D simulations for the sintering of two particles in 3D. Abstract: Selective laser sintering (SLS) is an important additive manufacturing method for polymers and is increasingly used for industrial applications. To improve the quality of printed products a thorough understanding of the process is necessary. Simulations are a convenient way to assess the sintering in detail. In literature several numerical studies can be found on the sintering process of two particles. Both 2D and 3D geometries are used and sometimes the assumption of axisymmetry is made. If the effect of the laser beam in temperature-dependent sintering is taken into account, axisymmetry cannot be assumed anymore and full 3D simulations are required. However, these simulations are complex and computationally expensive. In this work, we assess if 2D simulations are representative for the 3D case of the temperature-dependent sintering process of two viscous particles. We find that 2D simulations are a good alternative for 3D simulations for the sintering problem of two particles, if the correct geometrical scaling factors are taken into account.